Materiali per un commento a Gli strumenti umani di Vittorio Sereni - Cattaneo, Michel (L’ospite ingrato, 2021)
The article offers some ideas to prepare a commentary on Vittorio Sereni’s Gli strumenti umani. The cases of two poems are taken as an example. The first is Una visita in fabbrica. For this poem is proposed a new source. The second poem is Intervista a un suicida. The discussion here focuses on the identification of the protagonist. Moreover, notice on unpublished manuscripts related to the title of the collection is given.